2014
DOI: 10.1016/j.resuscitation.2014.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Postconditioning at the Initiation of CPR Improves Myocardial and Mitochondrial Function in a Pig Model of Prolonged Untreated Ventricular Fibrillation

Abstract: Background Anaesthetic postconditioning (APoC) attenuates myocardial injury following coronary ischaemia/reperfusion. We hypothesised that APoC at the initiation of cardiopulmonary resuscitation (CPR) will improve post resuscitation myocardial function along with improved mitochondrial function in a pig model of prolonged untreated ventricular fibrillation. Methods In 32 pigs isoflurane anaesthesia was discontinued prior to induction of ventricular fibrillation that was left untreated for 15 min. At the init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 49 publications
(55 reference statements)
1
25
0
Order By: Relevance
“…Sevoflurane, a commonly used inhalation anaesthetic agent in clinical practice, is considered the cornerstone of this drug class because of its favourable characteristics, including smooth induction of anaesthesia, rapid post-operative recovery and minimal impact on hemodynamics. Several studies have demonstrated that SpostC can protect healthy myocardium from I/R injury, [6][7][8][9]28 but the underlying mechanism remains unclear. Interestingly, our previous studies found that the protective effects of SpostC on isolated myocardial mitochondria can be attributed to the upregulation of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sevoflurane, a commonly used inhalation anaesthetic agent in clinical practice, is considered the cornerstone of this drug class because of its favourable characteristics, including smooth induction of anaesthesia, rapid post-operative recovery and minimal impact on hemodynamics. Several studies have demonstrated that SpostC can protect healthy myocardium from I/R injury, [6][7][8][9]28 but the underlying mechanism remains unclear. Interestingly, our previous studies found that the protective effects of SpostC on isolated myocardial mitochondria can be attributed to the upregulation of HIF-1a.…”
Section: Discussionmentioning
confidence: 99%
“…5 Sevoflurane is an ideal inhaled anaesthetic agent that is widely used in peri-operative anaesthesia. [6][7][8][9] Unfortunately, diabetes abolishes the cardioprotective effects of SpostC, [10][11][12] and the underlying mechanism remains unclear. [6][7][8][9] Unfortunately, diabetes abolishes the cardioprotective effects of SpostC, [10][11][12] and the underlying mechanism remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the conclusion of the experimental protocol, mitochondria were isolated at 4°C via differential centrifugation from the left ventricle of the heart and brain as described previously(12,13). State 3 (S3) and State 4 (S4) respiration, the rate of ATP synthesis, and calcium retention capacity (CRC) were quantified as previously described(12).…”
Section: Methodsmentioning
confidence: 99%
“…State 3 (S3) and State 4 (S4) respiration, the rate of ATP synthesis, and calcium retention capacity (CRC) were quantified as previously described(12). The respiratory control index (RCI) was calculated as the ratio of S3 to S4 respiration.…”
Section: Methodsmentioning
confidence: 99%